PEMAKNAAN SYAIR LI KHAMSATUN DI TENGAH PANDEMI COVID-19 PERSPEKTIF LIVING ISLAM - Zuhri, H. (Living Islam: Journal of Islamic Discourses, 2020)
This research explores the historical dimensions and the episteme phenomena in spreading the recitation of the Khamsatun poem in the middle of the Javanese Muslim community in the face of the COVID-19 pandemic. Historically, this poem has functioned as a means to invoke protection from epidemics in the form of reviving religious rituals in people's social beliefs. Therefore, to find the social meaning of this poem, this research uses the Hans-Georg Gadamer hermeneutic approach in seeing the mediation of community understanding related to the meaning of poetry. This study concludes that Islam responds to various incidents that befall their followers in various ways, one of which is to ask for protection from the plague through prayer in the form of poetry. Lil Khamsatun Poetry is identical as a ritual of Dhikr in the Sha Dhiliyah Tariqah is objectified in the community, so they feel safe and protected from COVID-19. This process shows that the facts about COVID-19 are not enough just to be seen from a rational and health perspective but also it can be seen as a phenomenon of the response of the Muslim community to the epidemic through reviving religion in social life.